Design, Fabrication, and Performance Evaluation of Wood Shredder Using 2-Blade, 3-Blade, and 4-Blade Cutting Discs - Wirotecheewan, Prasert; Chindaprasert, Nataporn; Wiangthong, Thanaphon; Tinprabath, Padipan (RMUTP Research Journal Sciences and Technology, 2025)
This research aims to design, fabrication, and test a mobile wood shredder. The effect of the number of blades on the ability to shred wood branches was studied. Testing was conducted on wood pieces with a diameter not exceeding 70 millimeters, using both fresh and dry wood branches weighing 15 kilograms per test. Three sets of blades were utilized: 2-blade, 3-blade, and 4-blade sets, with a cutting angle of 45 degrees and a blade length of 105 millimeters. The tests were conducted at an engine speed of 3,400 revolutions per minute. The test results revealed that the wood shredder could shred fresh wood faster than dry wood, and increasing the number of cutting blades reduced the shredding rate. The shredding rates for fresh and dry wood with the 2-blade cutting discs were 274.3 and 221.4 kg/h, respectively, followed by the 3-blade cutting discs at 250 and 216.3 kg/h and the 4-blade at 221.7 and 178.6 kg/h, respectively. Moreover, increasing the number of blades resulted in smaller and finer wood chips, with the maximum sizes after shredding being 15x25, 10x15, and 7x10 mm for the 2-blade, 3-blade, and 4-blade cutting discs, respectively. Additionally, it was found that the wood shredder with 4-blade cutting discs had lower shredding rates compared to the shredder with 2-blade cutting discs.